Argia mauffrayi n. sp. from Ecuador (Odonata: Coenagrionidae) - Garrison, Rosser W.; Cabrera, Giovanni M. Ramón (Zootaxa, 2019)
Argia mauffrayi n. sp. (Holotype ♂: ECUADOR, Pichincha Province, San Miguel de Los Bancos Cantón, Recinto Milpe, Milpe Bird Sanctuary, Mirador Uno Trail, 0.0333° N, 78.8661 W, 4 ix 2018, William F. Mauffray leg., in Laboratorio de Zoología Terrestre USFQ [ZSFQ]) is described and illustrated and compared with similar species.